2003
DOI: 10.1177/0886109903018002006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diversity of Women Veterans' Identity to Improve the Delivery of Veterans' Health Services

Abstract: This qualitative study explored the domains of gender, ethnicity, and military association in a population of women veterans as these domains related to the women's access to and use of health care services and assessed barriers to the use of health services and suggestions for improving them. The study found that a significant proportion of the participants had experienced some form of gender discrimination in the military, through segregation or sexual harassment, and that their perceptions of the Veterans A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…This suggests that although prototypic experiences may be associated with greater veteran identity centrality, they may also be associated with decreases in positive regard for veteran identity when they reflect more negative aspects of that identity. This is consistent with prior research suggesting that women who have experienced gender discrimination or sexual assault while deployed (components of deployment sexual harassment) may be simultaneously more likely to use VHA services and less likely to feel positively about their experiences in VHA (Huynh-Hohnbaum et al, 2003; Kelly et al, 2008) than women who have not had these experiences. In addition, these findings are consistent with the broader collective self-esteem literature, which suggests that negative experiences such as discrimination may increase identification, but may decrease self-esteem around an identity (e.g., Branscombe et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that although prototypic experiences may be associated with greater veteran identity centrality, they may also be associated with decreases in positive regard for veteran identity when they reflect more negative aspects of that identity. This is consistent with prior research suggesting that women who have experienced gender discrimination or sexual assault while deployed (components of deployment sexual harassment) may be simultaneously more likely to use VHA services and less likely to feel positively about their experiences in VHA (Huynh-Hohnbaum et al, 2003; Kelly et al, 2008) than women who have not had these experiences. In addition, these findings are consistent with the broader collective self-esteem literature, which suggests that negative experiences such as discrimination may increase identification, but may decrease self-esteem around an identity (e.g., Branscombe et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Given this history, individuals within and outside of the veteran community may be less likely to think of women as veterans. Indeed, qualitative research with female veterans has suggested that female veterans are often assumed to be civilians (Huynh-Hohnbaum, Damron-Rodriguez, Washington, Villa, & Harada, 2003). This is problematic, given that previous research has identified concerns about fit within VA as a barrier to women using VA mental health services (Owens, Herrera, & Whitesell, 2009).…”
mentioning
confidence: 99%
“…The VA serves as a tertiary prevention service through provision of mental and medical health care, employment and educational opportunities, and housing and economic supports, yet only a portion of women veterans utilize VA services. Addressing a historical lack of service to women (Huynh-Hohnbaum, Damron-Rodriguez, Washington, Villa, & Harada, 2003), the VA has recently increased its outreach and coordination of care for women veterans through programs such as the Women Veterans Call Center and Women Veteran Program Managers at each VA Medical Center. Nongovernmental organizations that provide care to women veterans can also provide services to mitigate the losses associated with premature separation.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, female veterans do not always perceive they are eligible for VA services. This perception is amplified by a lack of gender-specific health care for female veterans in the VA health-care system (Huynh-Hohnbaum, Damron-Rodriguez, Washington, Villa, & Harada, 2003). The VA health-care system reproduces and perpetuates the gendered hierarchy that shapes women’s active duty service.…”
Section: Methodsmentioning
confidence: 99%
“…Contemporary feminist scholarship stresses not only gender but intersectionality—that is, how gender intersects with other categories of difference, such as ethnicity, race, sexuality, citizenship, class, age, disability, or geographic location (Ackerly & True, 2008). There is recognition in the emerging veterans literature of the need to pay more attention to the intersecting identities and specific needs of a diverse veterans population but intersectionality represents a major gap in this body of research (Huynh-Hohnbaum et al, 2003). An intersectional approach would recognize the significance of gender without overstating it and be able to capture the lived and diverse realities of veterans.…”
Section: Methodsmentioning
confidence: 99%